The Flinders University/TAFE SA Bachelor of Creative Arts dual award model : A case study. - Gander, Michelle; Bouvet, Eric (Journal of University Teaching & Learning Practice v.20 n.7 https://doi.org/10.53761/1.20.7.04, 2023)
This study aims to evaluate the effectiveness of the Bachelor of Creative Arts (BCA), a dual award degree offered jointly by Flinders University and TAFE SA. It first sets the rationale for the award while placing it in the Australian educational context, comparing it to equivalent programs offered at other institutions. It then provides an insight into the characteristics of a cohort of students. To achieve this, the study analyses a range of key quantitative metrics including demographics, enrolment numbers, attrition, student experience surveys and grade distributions to determine the cohort's profile. Additionally, the study seeks information from recent graduates already in the workforce to establish if the BCA provides the skills leading to successful employment. This study reveals a mixed picture of the BCA's success. While degree completion and student satisfaction are high, alumni are not all convinced that having a university degree provides a significant advantage for the job market as opposed to only having a TAFE qualification. Finally, the study offers recommendations to address these issues and improve the overall student experience as well as enhance their employment prospects. [Author abstract]